2007
DOI: 10.1093/nar/gkm034
|View full text |Cite
|
Sign up to set email alerts
|

Translational repression of mouse mu opioid receptor expression via leaky scanning

Abstract: Mu opioid receptor (MOR) expression is under temporal and spatial controls, but expression levels of the MOR gene are relatively low in vivo. In addition to transcriptional regulations, upstream AUGs (uAUGs) and open reading frames (uORFs) profoundly affect the translation of the primary ORF and thus the protein levels in several genes. The 5′-untranslated region (UTR) of mouse MOR mRNA contains three uORFs preceding the MOR main initiation codon. In MOR-fused EGFP or MOR promoter/luciferase reporter construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…3), indicating that uATG Ϫ105 was recognized by the ribosome and inhibited the translation of the downstream ORF. These findings are consistent with most other findings that uATGs inhibit downstream ORF translation (Meijer et al, 2000;Diba et al, 2001;Kwon et al, 2001;Blaschke et al, 2003;Mihailovich et al, 2007;Song et al, 2007). Further studies showed that the amino acid sequence of the peptide encoded by uORF-105 was not important in regulating translation and that uORF-105 acted only as a cis element to inhibit downstream ORF translation.…”
Section: Translational Regulation Of Human Mrp2 243supporting
confidence: 91%
See 1 more Smart Citation
“…3), indicating that uATG Ϫ105 was recognized by the ribosome and inhibited the translation of the downstream ORF. These findings are consistent with most other findings that uATGs inhibit downstream ORF translation (Meijer et al, 2000;Diba et al, 2001;Kwon et al, 2001;Blaschke et al, 2003;Mihailovich et al, 2007;Song et al, 2007). Further studies showed that the amino acid sequence of the peptide encoded by uORF-105 was not important in regulating translation and that uORF-105 acted only as a cis element to inhibit downstream ORF translation.…”
Section: Translational Regulation Of Human Mrp2 243supporting
confidence: 91%
“…Alternatively, there may be internal ribosomal entry sites located in the 5ЈUTR, such that the translation machinery skips the uATGs and instead uses the internal ribosomal entry sites to initiate translation of the downstream ORF (Le and Maizel, 1997). Whereas some upstream start codons (uATGs) inhibit downstream ORF translation (Meijer et al, 2000;Diba et al, 2001;Kwon et al, 2001;Blaschke et al, 2003;Mihailovich et al, 2007;Song et al, 2007), other uATGs have no such effect (Diba et al, 2001). uORFs can also influence the stability of mRNA by a process termed nonsense-mediated mRNA decay (Hood et al, 2009).…”
mentioning
confidence: 99%
“…-Opioid receptor (MOR) mediates most of the pharmacological effects of opiates; its regulation is of great importance to unravel the molecular mechanisms underlying the physical responses to opioid treatment, such as tolerance and dependence. In addition to the multiple cis-acting elements that regulate the transcription of MOR (Hwang et al, 2004;Kim et al, 2006;Choi et al, 2007;Song et al, 2007), a recent study on the 3Ј-UTR of the major -opioid receptor mRNA (MOR1) has started to address the regulation of MOR at the post-transcriptional level (Wu et al, 2008).…”
mentioning
confidence: 99%
“…Several Oprm1 isoforms have been reported (9 -11). The upstream open reading frames in Oprm1 mRNA act as negative regulators through a ribosome leaky scanning mechanism (12).…”
mentioning
confidence: 99%